2004
DOI: 10.1029/2003jb002698
|View full text |Cite
|
Sign up to set email alerts
|

Paleomagnetic dating of burial diagenesis in Mississippian carbonates, Utah

Abstract: [1] The objective of this study is to test models for the origin of widespread secondary magnetizations in the Mississippian Deseret Limestone. The Delle Phosphatic Member of the Deseret Limestone is a source rock for hydrocarbons, and modeling studies indicate that it entered the oil window in the Early Cretaceous during the Sevier orogeny. Paleomagnetic and rock magnetic results from the Deseret Limestone and the stratigraphically equivalent Chainman Shale in central and western Utah indicate that the units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Two hypotheses are commonly put forward to explain chemical magnetic remagnetizations (CRM). Diagenetic reactions that destabilize clay minerals or organic matter during burial temperature increase and release Fe in solution (Katz et al, 1998;Katz et al, 2000;Blumstein et al, 2004). The second hypothesis appeals for more exotic fluids associated to large-scale migrations of orogenic fluids (Oliver, 1992) or water table fluids (Garven, 1995).…”
Section: Mechanisms For In Situ Formation Of Secondary Magnetitementioning
confidence: 98%
“…Two hypotheses are commonly put forward to explain chemical magnetic remagnetizations (CRM). Diagenetic reactions that destabilize clay minerals or organic matter during burial temperature increase and release Fe in solution (Katz et al, 1998;Katz et al, 2000;Blumstein et al, 2004). The second hypothesis appeals for more exotic fluids associated to large-scale migrations of orogenic fluids (Oliver, 1992) or water table fluids (Garven, 1995).…”
Section: Mechanisms For In Situ Formation Of Secondary Magnetitementioning
confidence: 98%
“…Katz et al, 2000) or maturation of organic matter (e.g. Banerjee et al, 1997;Blumstein et al, 2004) by burial alone. Several models for the origin of the CRM may be considered, including the migration of externally derived orogenic fluids (Oliver, 1992;Sears, 2001).…”
Section: Paleomagnetismmentioning
confidence: 99%
“…Lu et al 1991;Hirt et al 1993;Katz et al 1998Katz et al , 2000Gill et al 2002;Woods et al 2002;Zegers et al 2003;Blumstein et al 2004;Moreau et al 2005;Tohver et al 2008). Many of these studies incorporated presence/absence tests (e.g.…”
Section: Smectite To Illitementioning
confidence: 99%
“…7) is not related to syndeformational orogenic fluids (Fruit et al 1995). A study of the Mississippian Desert Limestone and Chainman Shale (Blumstein et al 2004), source rocks in western Utah, found a Jurassic CRM that was interpreted to have formed as a result of the maturation of organic matter based on the overlap between the timing of CRM acquisition and the timing of oil generation from modelling studies (Fig. 8).…”
mentioning
confidence: 99%